Formação continuada de professores: da parceria entre universidade e escola ao protagonismo e reconhecimento do trabalho docente - Mari Margarete Dos Santos Forster; Tatiane Costa Leite (Revista Diálogo Educacional, 2014)
University and school have rehearsed some experiences in partnership towards a more qualified teacher training. The research group has been experimenting this since 2001 through various investigative projects. The object of study is the initial and continuing training of teachers, reflecting on the knowledge produced in the practice of the craft of these professionals. Investigations have ethnographic character, are qualitative, highlighting the critical action-collaborative research; make use of discussion groups, records of experiences, documentary analysis, observation and interviews. Findings of the research: university and school spaces are rich in contradictions; subjects that take part in there have what to say, produce knowledge that need to be recorded, valued, publicized; the way how institutions work can be facilitators or cause difficulties on learning and professional development; professionals graduate in their workspace and change it; dialogue and reflection are presented as primordial in achieving learning spaces; shared spaces for reflection and questioning facilitate the professional development process, are formative and can result in professional learning; the continued educational work and the identification of its benefits to the classes and the students favor learning and professional development; the positive and purposeful welcoming from directive team to the teacher’s work, listening and valuing it favors the development of professionals learning; change of representations and discourses of teachers may be accompanied by changes in teaching practices and the partnership University/College/University may maximize more qualified teaching actions.